Pengaruh citra merek, kepercayaan merek, dan kualitas layanan pada loyalitas merek pakaian ZARA - Vika Mitra Ifana; Tatik Suryani (STIE Perbanas Surabaya, 2016)
The clothing industries in Indonesia are becoming more and more competitive. Many brands of clothes avalaible in the market place have a good quality and popularity. ZARA was one of clothes famouse in Indonesian. This Study aims to examine the effect of brand image, brand trust, and service quality on brand loyalty of ZARA clothes. Data coleccted by questionnare and involved 100 consumers in Surabaya. The sample was was selected by judgement sampling. The data were analyzed using MRA (Multiple Regression Analysis).The result shows that brand image has significant effect on brand loyalty, brand trust has signifcant effect on brand loyalty, and service quality has significant effect on brand loyalty. It implies that, it is important to improve brand image, trust and service quality for creating customer loyalty. Promotional strategy by delivering message honesty is important for building image and trust. Service quality can improve the overall service quality. The company should improve the product quality and services by improving attitude, skill and knowledge it’s employees.